Manajemen Pelayanan Pajak Di KPP Pratama Jakarta Matraman - Lutfiah Solehah Askandar; Selvi Selvi (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The purpose of this study is to analyze the management of tax services at KPP Pratama Jakarta Matraman, the obstacles that arise in the management of tax services at the Primary Tax Office of Matra-man, Jakarta, and the efforts made by the Primary Tax Office of Matraman, Jakarta in overcoming these obstacles. In this study, the author analyzed the data using a qualitative descriptive method based on a case study, where the author conducted in-depth inter-views with informants and collected as much data as possible for re-view. The results of this study indicate that the management of tax services carried out by the Primary Tax Office of Matraman, Jakarta is good in terms of organization but not optimal in terms of planning due to new policy constraints that require taxpayers to reduce inter-actions with tax office employees due to the Covid-19 pandemic. The author suggests that the Primary Tax Office of Matraman, Jakarta pay attention to the performance of its employees, especially in tax services to the community, one of which is by controlling every achievement of the performance of its employees who work in the office or from home in order to realize optimal service to the commu-nity.